(3caGjI GdEfSGf ajeG jMJGL Edjg aj UdhJg ef GdeaSOI hGdUMI hGdTQGjW hGdCQcGfs - (3GHf GdjGRLj, ESeGYjd Hf YHO GdHGbj Hf ESeGYjd, J (B1121 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; hHYO ajbhd ESeGYjd Hf YHO GdHGbj GdjGRLj gPg QSGdI CedjJgG aj GdWgGQI hGdUdhI hGdGYJbGO hSeJgG caGjI GdEfSGfs
(3BNQgG (B:s
(3aUd CQcGf GdUdhI GdbjGe hGdQchY eQI hGdSLhO eQJjf ddbGOQ hGdYGLR Yf GdbjGe deQV Ch cHQ jQcYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 317s
(3eYLe GdeDdajf (B1 / 368s
(3Sdc GdOQQ (B1 / 255s
(3gOjI GdYGQajf (B1 / 219s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs